Concavocorona, a new genus of the leafhopper subfamily Evacanthinae (Hemiptera: Cicadellidae), with description of a new species - Wang, Yang; Zhang, Yalin (Zootaxa, 2014)
Concavocorona, gen. n., is described and illustrated based on a new species C. supercilia sp. n. from Thailand. In addition, C. abbreviata (Jacobi, 1944), n. comb. from China is transferred to this genus from Cunedda Distant, and its male genitalia is described for the first time.